Nature's footprints in the desert - Pearce, Q. L. (Querida Lee); Pearce, W. J. (William Julian), 1952-; Bettoli, Delana (Englewood Cliffs, N.J. : Silver Press, 1990)
Briefly describes the behavior of such desert animals as the tortoise, prairie dog, gila monster, and coyote.
School Library Journal
2.6
K-3
Keywords: Desert fauna -- Juvenile literature; Desert fauna -- North America -- Juvenile literature; Desert animals; Desert animals